ESG metrics and social equity: Investigating commensurability - Keeley, Alexander R.; Chapman, Andrew J.; Yoshida, Kenichi; Xie, Jun; Imbulana, Janaki; Takeda, Shutaro; Managi, Shunsuke (Frontiers in Sustainability, 2022)
During the past two decades, the world has seen exponential growth in the number of companies reporting environmental, social, and governance (ESG) data, and various ESG metrics have been proposed and are now in use. ESG metrics play a crucial role as an enabler of investment strategies that consider ESG factors, which are often referred to as “ESG investments”. The ESG metrics and investment market are evolving rapidly, as investors, corporations, and the public are giving more priority to the “S” in ESG, including social equity issues, such as diversity, income inequality, worker safety, systemic racism, and companies’ broader role in society. In this critical, systematic review, utilizing in-depth assessments, we investigate and compare the approaches employed in major ESG metrics and studies, then, we shed light on the “S” aspect by reviewing existing approaches used to assess social equity to clarify commensurability with ESG. Through the systematic review, this paper confirms that ESG investments can be expected to provide stable and high returns especially over the long term. This paper also clarifies how elements considered in social equity studies are largely reflected in major ESG metrics.